Probing of ferrocenylanilines on model micelle/reverse micelle membrane and their enhanced reactivity for reactive oxidants. (17th April 2018) - Altaf, Ataf A.; Badshah, Amin; Lal, Bhajan; Murtaza, Shahzad; Chatterjee, Pabitra B.; Akbar, Kamran; Crans, Debbie C.
Abstract : Reactive oxygen species are formed in the human body but can be removed by suitable antioxidants. In this study we synthesized and characterized three ferrocene derivatives, 4‐ferrocenylaniline (pFA), 3‐ferrocenylaniline (mFA) and 3‐methyl‐4‐ferrocenylaniline (MeFA), having significant potential to be used as antioxidants. The synthesized compounds are insoluble in water, with the solubility of these compounds increasing in micelle solution. The micelle and reverse micelle solutions were considered as model membranes. The synthesized compounds were probed on the model membranes, made by sodium dioctylsulfosuccinate reverse micelle and tetradecyltrimethylammonium bromide micelle, using 1 H NMR spectroscopy. The 1 H NMR results indicated that these compounds are present in the polar region of the model membrane interface. Quantitative measurements showed that mFA has the greatest ability to penetrate into the micelle membrane among these compounds, and pFA is least penetrating in this respect. Solubilization of these compounds in aqueous micelle solution facilitates crystallization (of mFA) and enhances the antioxidant potential of these compounds. X‐ray crystal structure analysis revealed that mFA captures water molecules during crystallization in micelle solution. Their ability to act as antioxidants was evaluated, in dimethylsulfoxide (DMSO) and in micelle solution, using standard 1, 1‐ diphenyl‐2‐picrylhydrazyl (DPPH) assay. It was found that their antioxidant potential is good in DMSO and that potential increases on the interface of the model membrane. The highest increase (by 19.6%) in the antioxidant potential, on the model membrane interface, was observed for mFA. Abstract : The synthesis and characterization of three ferrocene derivatives, 4‐ferrocenylaniline(pFA), 3‐ferrocenylaniline (mFA) and 3‐methyl‐4‐ferrocenylaniline (MeFA) was done with regard to their interactions with interfaces and their effects of the environment on reactivity against reactive oxygen species (ROS). The location of the compounds at the interface was examined using NMR spectroscopy. The less symmetric compounds were crystallized in the inhomogenous interfacial environment capturing a water molecule and documenting the presence of H2 O in these hydrophobic environments.